EKOTHE: Developing The Creative Economy Through Corn Silk Herbal Tea Processing - Astriya Indah Sari; Kholifatun Khasanah; Putri Aprilia Safara; Faidatul Masyruroh; Adinda Putri Dwi Lestari; Sri Rejeki Dwi Astuti (Al-Qalam Institute, 2025)
Serut Village is one of the agricultural villages in Jember where most of the residents work as farmers, especially corn farmers. The corn harvest is always sold raw, resulting in the accumulation of corn harvest waste such as corn husks and corn silk, even though both types of waste still have many uses if processed into products such as herbal tea that helps relieve urinary tract problems, prevent kidney stones, lower blood pressure, and help control blood sugar. Therefore, this activity aims to improve the skills of the Serut Village community in processing waste into marketable products, supporting the utilization of local resources, and introduce processed corn silk tea (EKOTHE) as a healthy alternative beverage. The implementation method for implementing the corn silk processing program into herbal tea is divided into three stages: pre-program, program implementation, and post-program. The results indicate an improvement in community skills in processing herbal products, the establishment of creative business groups, and increased awareness of the added value of agricultural waste. This innovation is expected to serve as a model for developing a local-based creative economy while enhancing the welfare of rural communities.